Development of Fiber-Optic Humidity Sensor Probe with Gelatin Cladding - Maddu, Akhiruddin; Modjahidin, Kun; Sardy, Sar; Zain, Hamdani (Makara Journal of Technology, 2006)
Development of Fiber-Optic Humidity Sensor Probe with Gelatin Cladding. Humidity sensor based on optical fiber with gelatin cladding has been developed. In this humidity sensor probe, the origin cladding of optical fiber is replaced by gelatin coating as humidity sensitive cladding. Testing of the optical fiber sensor probe was conducted by measuring of light intensity transmitted on the optical fiber probe for each variation of different humidity treatments. Response of the optical fiber sensor probe measured from 42%RH to 99%RH, the results show an optical transmission curve varied with relative humidity (RH). Optical transmission in the optical fiber probe increase with RH value at a specific wavelength range, that is from green to red spectrum bands (500 nm – 700 nm), where a significant variation from 600 nm to 650 nm in yellow to red spectrum bands. Wavelength where is a maximum intensity of optical transmission occurs at 610 nm. Therefore, the optical fiber humidity sensor probe could response humidity form 42%RH to 99%RH with the best response in humidity range of 60%RH to 72%RH that is have a good linearity and sensitivity.